Mycobacteroides abscessus subspecies: a comparative genomic analysis reveals unique metabolic activities and drug resistance patterns - Xiaoyu Wang; Yongdong Dai; Xiao Wang; Lingfei Li; Yanhai Feng; Shunying Liu; Zhenyu Kou; Liang Wang; Fangjie Wang; Yaokai Chen; Xia Lei (BMC Microbiology)
Abstract Background Mycobacteroides abscessus poses a considerable and growing threat to public health due to its resistance against most antibiotics and low cure rate. For a comprehensive understanding of the genomic characteristics and drug resistance mechanisms of M. abscessus, clinical isolates from diverse sources were collected and analyzed. Results The clinical M. abscessus complex analyzed herein primarily comprised two subspecies: Mycobacteroides abscessus subsp. abscessus and Mycobacteroides abscessus subsp. massiliense. Furthermore, comparative genomic and single nucleotide polymorphism analyses revealed distinct metabolic activities among subspecies. Subsequent examination of core hub gene mutations confirmed the presence of distinct metabolic and biosynthetic pathways between M. abscessus subspecies, which may have contributed to their differential drug resistance and may aid in providing targeted interventions. Understanding this subtle genomic variation is crucial for improving treatment strategies and patient outcomes. Additional analyses identified potential novel amikacin and moxifloxacin resistance genes, offering a promising avenue for investigating M. abscessus drug resistance. Conclusions Through comparative genomic analysis, we revealed the unique metabolic activities of M. abscessus subsp. abscessus and M. abscessus subsp. massiliense, providing a scientific basis for future diagnostic and personalized management strategies. Identifying possible novel amikacin and moxifloxacin resistance genes within these subspecies offers insights for future drug development efforts and enhances our understanding of the mechanisms underlying M. abscessus drug resistance.